Integrated model of industrial robot for control applications - Osman, Johari Halim Shah (Penerbit UTM Press, 1992)
This paper deals with the development of an intergrated mathematical model of a robot manipulator. The model of the system comprises the mechanical part of the robot as well as the actuators and the gear trains. Two different approaches of deriving the integrated model are presented which results in two different forms of the integrated dynamic model of the robot manipulator in state space description. Both types of the integrated model are highly nonlinear, time varying, and represent a more realistic model of the robotic system. The integrated model and the approach are useful and suitable for dynamic analysis and control synthesis purposes, and will provide a more efficient approach to the real situation.